Hubungan Pola Asuh Orang Tua dengan Kedisiplinan Siswa Kelas Tinggi di Sekolah Dasar - sUNDARI sUNDARI; rukayah rukayah; sidrah afriani Rahman (JPPSD:Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
The problem in this study is the lack of student discipline.  Student discipline does not just arise, but there are parties who play a very important role in children's education, one of which is through parenting applied by parents. This research is a quantitative research with the type of correlational research which aims to determine the relationship between parenting patterns and high grade elementary school students' discipline. The results showed that obtained rx = 0.412 then the relationship between the two variables was classified at the level of relationship in the "medium" category, because it was in the range 0.40 - 0.599 and the tcount value was 3.73 and ttable was 1.67.  It turns out that the value of tcount is greater than the value of ttable, thus it can be concluded that there is a significant relationship between parenting patterns and the discipline of high-class students.  So, the better the parenting style applied, the better the student discipline will be.  Based on these conclusions, the impact of this study is known that good parenting will improve student discipline.